Effect of solution treatment on mechanical and corrosion resistance properties of Mg–Zn–Nd–xCa alloy. (6th December 2017) - Xu, Shumin; Teng, Xinying; Zhou, Guorong; Zhao, Degang
Abstract: The effect of solution treatment on compression mechanical and corrosion resistance properties of Mg–6Zn–0.5Nd– x Ca alloys has been investigated in the current study. The results show that with solution treatment, the corrosion rate of Mg–6Zn–0.5Nd– x Ca alloy was reduced to 1.51 mm yr −1 . The corrosion mechanism of Mg–6Zn–0.5Nd– x Ca alloys tend to be uniform corrosion because of the secondary phase particle is diffused into matrix. The fracture strength of Mg–6Zn–0.5Nd–0.3Ca alloy has been dramatically increased by about 68%. With Ca content increasing, grains are refined and the compression mechanical properties of cast alloys are gradually increased to some extent. The Mg–6Zn–0.5Nd–0.5Ca alloy shows great corrosion resistance than other studied alloys.